Designing an explanatory practice framework: Local food systems as a case. (November 2013) - Crivits, Maarten; Paredis, Erik
This article elaborates an explanatory framework for the role of consumption practices in transitions to (enhanced) sustainability in the food system. To develop an applied practice approach we combine the concept of 'practice' with that of 'niche/regime', adopted from contemporary sociology and transitions theory, respectively. This re-combination adds to the field of applied consumption research and describes consumption beyond the boundaries of individualist and structuralist models, as well as integrates a conceptualization of the a-linear reproduction of aligning and competing consumer practices. We illustrate the methodology by showing its application drawing on data of a niche in the Belgian food system. Elaborating on the social practice model based on Giddens ((1984) The Constitution of Society . Cambridge: Polity Press), Bourdieu ((1976 ) Outline of a Theory of Practice . New York: Cambridge University Press) and Spaargaren and Van Vliet ((2000 ) Lifestyles, consumption and the environment: The ecological modernisation of domestic consumption. Environmental Politics 9(1): 50–76), we designate a three-tiered framework that endeavours to describe consumption practices in terms of everyday routines and habits, integrating an agency perspective with a dual perspective on structure. Consumer interviews and focus groups combined with a system analysis of the context of the alternative food practice allowed a schematization of what it implies to be a carrier of the niche practice . The practice schematizations of this niche are then considered vis-à-vis a schematization of the regime practice . The comparison shows two essential aspects: it points out that (1) although qualitative and systemic differences are found between niche and mainstream practices, in both cases the perception of the carriers (i.e. consumers) on what they need to do is to an equal extent normalized, and (2) empirical results indicate that central conceptions in the contemporary food consumption discourse, such as convenience, can in real life be redrawn by entirely different sets of interconnected routines. We reflect on the methodology and give suggestions as to how consumption governance could orientate towards practices as complementary to the traditional focus on individual consumer behaviour and consumer norm targets.